PENGARUH MARKETING MIX DAN DIGITAL BANKING TERHADAP KEPUASAN NASABAH PADA BANK SYARIAH INDONESIA CABANG PEKALONGAN PEMUDA DI MASA PANDEMI - Mochamad Yusuf Kustinah; Muhammad Taufik Abadi; Rinda Asytuti (Universitas Muhammadiyah Prof Dr Hamka, 2022)
Bank Syariah Indonesia has a growing number of customers every year. The increase in customers is not matched by the quality of service in the form of customer satisfaction. Customer satisfaction is still an obstacle to maximizing Islamic banks' profits. This study aims to examine the effect of marketing mix and digital banking on customer satisfaction at Bank Syariah Indonesia Pekalongan Pemuda Branch during the pandemic. The sample used was 99 respondents from a population of 17,261. The sample uses an accidental sampling technique. The method uses a questionnaire. Instrument testing, classical assumption analysis, multiple linear regression analysis, and hypothesis testing were used to analyze the data. The results of the analysis conducted on customer satisfaction at Bank Syariah Indonesia Pekalongan Pemuda Branch during the pandemic, namely how digital banking variables affect customer satisfaction, However, the marketing mix has no effect on customer satisfaction. Keywords: Marketing Mix, Digital Banking, Customer Satisfaction